Práticas pedagógicas e saberes docentes : o que pensam professoras e professores da área de Ciências Humanas do Ensino Fundamental ll - Leão, Gizeli da Costa (2020)
The current study is linked to the Postgraduate Program in Education (PPGEdu) UFMT – Campus of Rondonópolis – MT, under supervision of Professor Dr. Ademar de Lima Carvalho. It has as theme the pedagogical practices and the teaching knowledge: what do teachers of the final years of basic education, in the public schools of the state system, in the city of Primavera do Leste/MT think of these. As for the main aim of the research was: analyzing the comprehension that the teachers have of pedagogy as necessary ground for the teaching practice. It were considered as specific aims: a) reflecting what they comprehend as pedagogical knowledge; b) comprehending how teachers learn the relevance of Pedagogy and their personal and professional development; c) investigating which authors the teachers study in order to ground their practice; d) determining if there is a relation of the studies in the teacher education environment which contributes to broaden the pedagogical practice. The research was conducted with qualitative approach and the dialectic method in the perspective of the Freirean view. The current study is underpinned theoretically to the critical pedagogy, and to the educating act of Paulo Freire. In the case of Pedagogy as science, it is a problem that this must solve, in other words, structure itself as science of the practice and for the practice. This has showed to be a difficult task, but there are possible routes, besides the criteria of validity of the science, in which expresses by the deliberate social practice, result of the engagement of man in their productive process. Theories are only transformed in pedagogical knowledge when they become expressions of the meanings clarified in the exercise of praxis. For data gathering, official documents and semi structured interviews were used. The analysis of the compiled data point out that the pedagogical practice of teachers of human sciences in the final years of basic education happens by means of the objective conditions of work and of the knowledge that the teacher has about it. It was also evidenced the relation with the education centered in the school, the pedagogical knowledge, and the importance of pedagogy as science of education. The result showed that, in order to transform your practice into instrument of analysis, reflection and comprehension, aligned to a theoretical framework, it is required awareness from the researched subjects.